Macrocystic Adult Penile Lymphangioma: A Rare Presentation - Jaisukh Kalathia; Kaushal Patel; Santosh Agrawal (Case Reports in Urology)
Adult penile lymphangioma (APL) is a rare multifactorial vascular malformation. Usually, it is asymptomatic and located on the coronal sulcus or shaft of the penis. It is benign in nature with rare chances of recurrence. APLs can be approached via various modalities from simple “watch and wait” to electrofulguration, laser ablation, and surgical excision. We report a rare variant of lymphangioma of the penis inculcating the shaft being excised surgically with favorable outcome along with brief review of literature.